Material samples and mock-up and test report and technical specification of water repellent (RFA-447_Rev E) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.